Weightlifting for children and adolescents: A narrative review - Pierce, K. C.; Hornsby, W. G.; Stone, M. H. (Sports Health: A Multidisciplinary Approach, 2022)
The involvement of youth in the sport of weightlifting and the use of weightlifting methods as part of training for youth sport performance appears to be increasing. Weightlifting for children and adolescents has been criticized in some circles and is a controversial aspect of resistance training for young people. Although injuries can occur during weightlifting and related activities, the incidence and rate of injury appear to be relatively low and severe injury is uncommon. A number of performance, physical, and physiological variables, such as body composition, strength, and power, are improved by weightlifting training in children, adolescents, and young athletes. Manipulating program variables, when appropriate, can have a substantial and profound influence on the psychological, physiological, physical, and performance aspects of weightlifters. An understanding of the sport, scientific training principles, and musculoskeletal growth development is necessary to properly construct a reasonable and appropriate training program. A scientific background aids in providing an evidenced basis and sound rationale in selecting appropriate methods and directing adaptations toward more specific goals and enables the coach to make choices about training and competition that might not otherwise be possible. If weightlifting training and competition are age group appropriate and are properly supervised, the sport can be substantially safe and efficacious.